KONSEP DIRI PRIA METROSEKSUAL DI KOTA PEKANBARU - Ramadhan, Icshan; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was carried out on the existing beauty clinics in the city of Pekanbaru. The purpose of this research is to know the concept of the self and the activity of the metrosexual in doing facial treatments as well as consumption patterns metrosexual in use of free time. The subjects in this study amounted to 5 people that is men who do facials. The author uses descriptive qualitative methods and data were analyzed qualitatively and retrieval technique using accidental sampling. Data instruments are observation, in-depth interviews and documentation. From the results of research conducted the author discovered that the metrosexual who perform facial treatments due to the wish to have a clean face of blackheads and spots of black flecks. Besides their goal of doing facial treatments because of demands from the place of work that requires them to look neat and clean. As for metrosexual consumption patterns in the use of free time, they perform activities shopping fashion branded and hunting accessories, hanging out at cafes, karaoke and doing fitness. It is done for menunjung his performance let me look perfect in front of others.Keywords: Men Metrosexual, Self Concept, Activity